2005
DOI: 10.1145/1073204.1073233
|View full text |Cite
|
Sign up to set email alerts
|

Interactive video cutout

Abstract: Input videosCutout objects Foreground objects composited together on new backgroundFigure 1: Our interactive video cutout system makes it easy to extract the foreground objects in these videos of an elephant and a skatebaorder. We then composite these objects onto a third background video to form a new video in which the skateboarder skates on the elephant. AbstractWe present an interactive system for efficiently extracting foreground objects from a video. We extend previous min-cut based image segmentation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
234
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(237 citation statements)
references
References 21 publications
0
234
0
3
Order By: Relevance
“…This work is motivated by recent advances in single image alpha matting where it has been shown that sparse information in the form of user brush strokes can be sufficient for figure-ground segmentation in many situations [30]. These results have been extended to video sequences, but to date have required considerable user interaction [32]. We show in this paper that sparse local information in the form of spatiotemporal T-junctions can remove the requirement for user interaction in many cases.…”
Section: Introductionmentioning
confidence: 94%
“…This work is motivated by recent advances in single image alpha matting where it has been shown that sparse information in the form of user brush strokes can be sufficient for figure-ground segmentation in many situations [30]. These results have been extended to video sequences, but to date have required considerable user interaction [32]. We show in this paper that sparse local information in the form of spatiotemporal T-junctions can remove the requirement for user interaction in many cases.…”
Section: Introductionmentioning
confidence: 94%
“…Interactive video object segmentation systems have been proposed in recent years. Various directions have been investigated such as tracking region boundaries over time [2,54], extending 2D segmentation to 3D video volumes [43,66,3,4], applying graph cut segmentation on successive frames driven by motion flow [6,5,70,68]. Our algorithm propagates the foreground mask forward which initializes the segmentation on the new frame and provides a shape prior taking account of the inherent error in optical flow.…”
Section: Related Workmentioning
confidence: 99%
“…Global color models. Some modern interactive video cutout systems use global color models, such as the popular choice of global Gaussian mixtures (GMM), to represent the appearance of the dynamic objects, e.g., [2][3][4]. Global color models do not consider the spatial arrangements of color components, thus are robust to object motion.…”
Section: Related Workmentioning
confidence: 99%
“…Similar to the foreground modeling, the DCF model is applied to the reconstructed clean plate, except that σ i is fixed for every background pixel. Typically for static background σ i is set to [2,4] to compensate for small alignment errors. Progressive Background Completion.…”
Section: The Background Layermentioning
confidence: 99%